2019
DOI: 10.1177/0969141319885409
|View full text |Cite
|
Sign up to set email alerts
|

Cervical screening in Western Kazakhstan: Liquid-based cytology ‘Cell Scan’ versus azur-eosin staining

Abstract: Objective To assess the effectiveness of the current cervical cancer screening tools in Western Kazakhstan. Methods Smears taken through (i) conventional cytology using azur-eosin staining and (ii) liquid-based cytology (LBC) ‘Cell Scan’ in the general female population and in women first diagnosed with cervical cancer were collected throughout the region. ROC-analysis with curve construction and weighted Cohen's κ calculation were applied. A total of 494 cytological pairs were collected, including 94 sets wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(20 reference statements)
0
9
1
Order By: Relevance
“…In the second study conducted in Western Kazakhstan, the prevalence of HPV was found to be 25%, and the most common HPV genotypes were HPV-16 (26.40%), HPV- 31 (10.10%), HPV-51 (9.40%), HPV-52 (9%), and HPV-6 (7.90%). 22 The major subtypes resulting in high-risk HPV infection types in Jinhu area were 52, 58, 16, 53, 56, and 33, which was not consistent with previous reports on different subtype infection rates across most regions of China. HPV16, together with HPV 18, is known to be responsible for approximately 70% of cervical cancer cases worldwide.…”
Section: Discussioncontrasting
confidence: 83%
“…In the second study conducted in Western Kazakhstan, the prevalence of HPV was found to be 25%, and the most common HPV genotypes were HPV-16 (26.40%), HPV- 31 (10.10%), HPV-51 (9.40%), HPV-52 (9%), and HPV-6 (7.90%). 22 The major subtypes resulting in high-risk HPV infection types in Jinhu area were 52, 58, 16, 53, 56, and 33, which was not consistent with previous reports on different subtype infection rates across most regions of China. HPV16, together with HPV 18, is known to be responsible for approximately 70% of cervical cancer cases worldwide.…”
Section: Discussioncontrasting
confidence: 83%
“…In our pilot study conducted in 2017 the overall HR-HPV prevalence was 43.6% and HPV-33, HPV-51 and HPV-52 were the most prevalent [ 6 ]. Another study published in 2019 found 25% HR-HPV positive patients, and among the most prevalent HR-HPV genotypes were HPV-33 (4.9%), HPV-51 (4.9%) and HPV-52 (4.9%) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 Kazakhstan exhibits a high CC incidence rate in women of all ages, and it has risen significantly to 18.2 per 100,000 women. 3 , 4 The age-standardized incidence and mortality were 15.7 and 7.5 per 100,000 women, respectively (estimates for 2018). 3 About 1729 new CC cases are diagnosed annually in Kazakhstan, and CC ranks as the second leading cause of cancer and cancer-related death in women.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 7 The Kazakhstani national screening programme has undergone significant positive changes over the past 12 years since it was implemented in 2008. 4 Initially, based on conventional Papanicolaou testing (Pap smear), screenings were performed every 5 years in the target group of women aged 30–60 years. 4 From December 2017, the screening interval was reduced to 4 years, and the age of the target group was extended to 70 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation